Ultra-fast laser pulses induced phase changes in ηǦMo4O11 crystals - Borovšak, Miloš; Mihailović, Dragan (Anali PAZU, 2022)
The article presents the experimental result of fluence dependence of the transient reflectivity response to ultra-fast laser pulses in η-Mo4O11 crystals. Results of the experiment show that at certain fluences at low temperatures phase changes can be induced in the crystals which are not seen  inthe temperature phase diagram.
Keywords: ultra-fast optical spectroscopy; molybdenum oxides; phase changes